Uji Ekstrak Enatol 70% Daun Sirih (Piper Betle L.) Terhadap Bleeding Time Pada Mencit Jantan Galur Swiss Webster - Sutopo, Tri (2016)
Background:Betel plant (Piper betle L.) contains tannins and flavonoids,it was considered to have an effect as a hemostatic agent/cessation of bleeding. Objective: To determine the effect of the 70% ethanol extract of betel leaf (Piper betle L.) on bleeding time and to determine the concentration of extract which can give maximum decrease effect of bleeding time. Methods: This study was experimental laboratory method with Post Test Only With Control Group Design. The animals that used were 25 male Swiss Webster mice 2-3 months old, weight 20-30 grams, and were divided into 5 groups: negative control group was given sterile distilled water, Positive Control group was given epinephrine 1:1000, the first, second and third treatment group was given ethanol extract of betel leaf with concentration of 10%, 20%, and 40% respectively. Each group was calculated of the bleeding time using the Duke method. The data was analyzed with one-way ANOVA test and LSD (Least Significant Difference) test. Results: Ethanol extract of betel leaf with concentration of 10%, 20%, and 40% can decrease bleeding time with mean value of bleeding time in a row was 124.60 seconds, 104.80 seconds and 92.60 seconds. One-way ANOVA test showed that there were significantly difference mean of bleeding time in the five groups after given treatment, p = 0.000 (p <0.05). Conclusion: The ethanol extract 70% of betel leaf (Piper betle L.) concentration of 10%, 20%, and 40% could decrease bleeding time in male Swiss Webster mice. While the concentration of 20% and 40% had maximum decrease effect of bleeding time. Keywords: ethanol extract of betel leaf (Piper betle L.), bleeding time 1The Student of Medical Faculty, Muhammadiyah Surakarta University 2The Lecturer of Medical Faculty, Muhammadiyah Surakarta University